Characterization and manipulation of Corticothalamic neurons in associative cortices using Syt6‐Cre transgenic mice. Issue 7 (23rd October 2021) - Vaasjo, Lee O.; Han, Xiao; Thurmon, Abbigail N.; Tiemroth, Alina S.; Berndt, Hallie; Korn, Madelyn; Figueroa, Alexandra; Reyes, Rosa; Feliciano‐Ramos, Pedro A.; Galazo, Maria J.
Abstract: Corticothalamic interactions between associative cortices and higher order thalamic nuclei are involved in high‐cognitive functions such as decision‐making and working memory. Corticothalamic neurons (CTn) in the prefrontal cortex and other associative areas have been much less studied than their counterparts in the primary sensory areas. The availability of characterized transgenic tools to study CTn in associative areas will facilitate their study and contribute to overcome the scarcity of data about their properties, network dynamics, and contribution to cognitive functions. Here, we characterized the Syt6‐Cre (KI148Gsat/Mmud) transgenic mouse line, by tracking expression of a Cre‐mediated reporter. In this line, Cre‐reporter is strongly expressed in the prefrontal, motor, cingulate, and retrosplenial cortices, as well as in other brain areas including the cerebellum and the olfactory tubercle. Cortical expression starts embryonically and reaches the adult expression pattern by postnatal day 15. In the cortex, Cre‐reporter is expressed by layer 6‐CTn and by layer 5‐CTn to a lesser extent. We quantified Syt6‐Cre + CTn axon varicosities to estimate the distribution and density of putative corticothalamic driver and modulator inputs to thalamic nuclei in the medial, midline, intralaminar, anterior, and motor groups. Also, we characterized the effect of optogenetic stimulation of Syt6‐Cre + neurons in the activity of the prefrontal cortex. CTn stimulation in the prefrontal cortex induces an oscillatory activity in the local field potential that resembles the cortical downstates typically observed during slow‐wave sleep or quiet wake. Abstract : Our work highlights the potential of the Syt6‐Cre transgenic mouse line to effectively target Corticothalamic neurons in the associative cortices. This detailed study describes and tests the utility of the system, laying the foundation for its implementation as a new tool to study corticothalamic interactions between frontal and medial associative areas, thalamic nuclei, and the contribution of these interactions to higher cognitive functions.